A novel system for measurement of types and densities of sulfur crosslinks of a filled rubber vulcanizate. (April 2015) - Choi, Sung-Seen; Kim, Eunha
Abstract: A novel system for measuring the crosslink densities of mono-, di- and polysulfides of a filled rubber vulcanizate was developed. The system included pre-swelling, cleavage of sulfur crosslinks by a chemical probe using thiol/ n -hexylamine instead of thiol/piperidine, and two step swelling. A sample cage made of stainless steel mesh was used to measure multiple samples at the same time and to reduce experimental errors. The organic materials-extracted sample was pre-swollen in toluene to introduce the probe chemicals more rapidly and homogeneously into the whole network. Polysulfidic crosslinkages were cleaved by a chemical probe of propane-2-thiol/ n -hexylamine in toluene, while di- and polysulfidic crosslinkages were dissociated by a chemical probe of n -hexanethiol/ n -hexylamine in toluene. The experimental errors were lower than 2%. By using cubic apparent crosslink density, fractions of the crosslink types of an unknown rubber vulcanizate could be estimated even although the filler content and rubber composition are not analyzed.